2013
DOI: 10.4103/2230-8210.119631
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of severe bilateral emphysematous pyelonephritis: Case series and review of literature

Abstract: Emphysematous pyelonephritis (EPN) is a life-threatening condition most commonly observed in diabetes, with nephrectomy believed to be the treatment of choice. However, nephrectomy in EPN is associated with increased risk of complications secondary to associated hemodynamic instability and may result in lifelong hemodialysis in case of bilateral EPN. We present three patients of severe bilateral EPN and one patient of unilateral EPN with diabetic ketoacidosis (DKA) successfully managed conservatively. Patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 14 publications
1
18
0
2
Order By: Relevance
“…In contrast, other studies suggested that PCD is a quite effective and adequate approach with a high success rate even in extensive EPN. [ 3 4 11 12 13 14 15 16 22 23 ] which is in accordance with our study where patients managed conservatively had a good outcome and survived. Furthermore, two patients with class I and class IV treated primarily with DJ stent showed improvement similar to those treated with nephrostomy.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, other studies suggested that PCD is a quite effective and adequate approach with a high success rate even in extensive EPN. [ 3 4 11 12 13 14 15 16 22 23 ] which is in accordance with our study where patients managed conservatively had a good outcome and survived. Furthermore, two patients with class I and class IV treated primarily with DJ stent showed improvement similar to those treated with nephrostomy.…”
Section: Discussionsupporting
confidence: 92%
“…[ 1 6 7 9 10 17 18 ] Recent articles revealed that nephrectomy is associated with higher morbidity and mortality one of which was a systematic review that demonstrated 13.5% mortality in patients treated with PCD compared with 50% mortality for emergency nephrectomy. [ 3 5 7 8 16 22 ] In our series, the mortality was definitely higher with those who underwent nephrectomy. The overall mortality was 37.5% which was associated with those who had undergone nephrectomy, while those who were treated conservatively had a good outcome compared to those who had undergone nephrectomy.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations